Audit Committee Characteristics and Financial Restatements: Evidence from Two-Tiered System - Melyana Handoko; Tarsisius Renald Suganda; Rino Tam Cahyadi (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to examine the relationship between audit committee characteristics and the occurrence of financial restatements in Indonesia’s Consumer Business, Energy, and Manufacturing sectors, with a focus on the unique context of Indonesia as the research setting. Financial restatements, often referred to as an "accounting trust crisis," indicate weak corporate governance and the presence of agency conflicts within firms. Grounded in Agency Theory, this research investigates whether inherent attributes of the audit committee influence the likelihood of financial restatements. The study utilizes annual reports and financial statements of companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, analyzing 1,547 firm-year observations using a binary logistic regression model. The first model examines the effect of audit committee characteristics—size, independence, meeting frequency, tenure, age, and political connections—on the likelihood of financial restatements. The second model incorporates gender diversity as a moderating variable to assess its influence on these relationships. The findings reveal that, in the Indonesian context, audit committee independence and meeting frequency significantly increase the likelihood of financial restatements when gender diversity is not considered. However, when gender diversity is accounted for, committee size becomes a significant factor, suggesting that a larger committee only has an impact when female representation is present. These findings offer insights for firms and policymakers on the importance of strengthening corporate governance practices by considering audit committee attributes and advocating for gender diversity.